(untitled) (Journal of the College of Basic Education, 2022)
With the wide spread of the media, and the diversity of its channels, platforms and media, it was accompanied by a decline in the presenters of programs that ended with the weakness of the Arabic language, and the dominance of the local vernacular dialects over it. Which led to a sweeping attack and a sweeping invasion of the so-called (media language) on the classical language, and an overlap occurred between the classical language and the colloquial, resulting in a third hybrid language, and this third language, which became the approved media language is a status between the two levels, it is not the standard language in its rules, standards and structures. And its origins, nor is it a colloquial language that does not adhere to restrictions, is not subject to measurement and is not subject to provisions, and the danger lies in that it replaces the classical, and spreads with its weakness and corruption, and this language acquires legitimacy and is free for it, so it becomes the language of thought, literature, art, media and administration, any language life.In addition to the prevalence of foreign vocabulary in the discourse addressed to the Arab public. Indeed, these vocabulary have become the titles of famous programs and the names of stations widely spread in Arab countries. As well as the names of many shops, public markets, schools, universities and hospitals bearing foreign names to show off and boast, and the prevalence of errors in the Arabic language, the prevalence of melody on the tongues of its speakers, and the wide circulation of measures, structures, formulas and methods that are not related to the classical. This requires us to stand on the reality of the linguistic situation in the contemporary media discourse, at this stage filled with regional and international changes. It is not an exaggeration in the light of this to say that this situation is dangerous by all standards, or by all meanings, and from several aspects, but this danger does not prevent us from addressing the imbalance and purifying the linguistic environment in the media discourse from pollution, and making way for a linguistic development in which consideration is restored to the In classical Arabic, the state of language and the upgrading of the language of media discourse in the media.